2006
DOI: 10.1111/j.1600-6143.2006.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation in Indo-Asian Patients in the UK

Abstract: Membership of some ethnic groups has an effect on renal transplant outcome but little is known about the impact of Indo-Asian ethnicity, despite this group's high incidence of renal disease. We compared outcomes in Indo-Asians and Caucasians at the Hammersmith Hospital (Indo-Asians, N = 46; Caucasians, N = 90), in the Long-Term Efficacy and Safety Surveillance (LOTESS) database of cyclosporin-treated renal transplant recipients (Indo-Asians, N = 254; Caucasians, N = 4262) and the National Transplant Database h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
2
16
1
Order By: Relevance
“…This finding is in conformity to the general population (15). A previous study (8) showed that post-transplant BP and lipid levels in SAs are comparable to whites, although diabetes rates are higher. Our center tailors immunosuppressive regimen to NODAT risk (16), which may have served to equalize this risk factor as well.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is in conformity to the general population (15). A previous study (8) showed that post-transplant BP and lipid levels in SAs are comparable to whites, although diabetes rates are higher. Our center tailors immunosuppressive regimen to NODAT risk (16), which may have served to equalize this risk factor as well.…”
Section: Discussionsupporting
confidence: 89%
“…North American SAs have higher coronary heart disease mortality rates than individuals of either European or Chinese descent (6), have more severe disease (1), and may also present with disease at an earlier age (7). In the United Kingdom, a country with a large SA population, SA kidney transplant recipients show graft function and survival and patient survival rates that are comparable to whites (8). Traditional cardiovascular risk factor prevalence is similar, with the exception of diabetes (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,3] Nevertheless, tacrolimus is associated with improved graft and patient survival, and with a significantly reduced risk of acute rejection and steroid resistant acute rejection. [3][4][5] Besides calcineurin inhibitors, a number of risk factors for PTDM have been identified, including: non-white ethnicity, [1,3,[6][7][8] pulse steroid treatment for acute rejection, [1] chronic hepatitis C virus infection (HCV) [3], and female gender [1,3]. Some argue that it would be advisable to avoid the use of tacrolimus in patients who are already at high risk of PTDM because of non-modifiable risk factors, such as non-white ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although Indo-Asian patients also had longer waiting times and poorer HLA match, outcomes were similar to Caucasian patients. Dooldeniya et al [6] compared the outcomes in Indo-Asians and Caucasian patients at the Hammersmith Hospital, London, and in the UK National Transplant Database, and found that co-morbid conditions in the two groups were similar, except a significantly higher incidence of diabetes in the Indo-Asian groups. After transplant, the incidence of delayed graft function, rejection episodes, graft and patient survival were similar.…”
Section: Introductionmentioning
confidence: 99%